NUMERICAL SOLUTIONS FOR STEADY FLOW PAST A CIRCULAR CYLINDER VIA THE METHOD OF VARIATIONAL IMBEDDING (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1998)
A numerical investigation of the two-dimensional flow around a circular cylinder is performed using a primitive-variable approach. Steady (but unstable) solutions have been calculated up to Re = 200. The imbedding system is solved numerically by a difference scheme of splitting type. A staggered non-uniform grid is used. The obtained results are in good agreement with the available data.